The connotations of composition in the works of the potter Nasser Al-Halabi ((Analytical study)) (Al-Academy, 2025)
The research aims: to reveal the connotations of composition (natural, cultural) in the artist’s works. The limits of the research were: the objective limit: studying the connotations of composition by the potter Nasser Al-Halabi, the spatial limit: Lebanon, and the temporal limit: 1993 - 2017. The terms that appeared in the title of the research were defined, which are: (connotation, composition). The second chapter also included the theoretical framework, and included two sections:The first topic :. Diversity of composition elements and its artistic applications. Formation in ceramic art, the concept of significance, significance in ceramic work.The second topic: Contemporary Lebanese ceramics.This was followed by studies of the precedent and the indicators that resulted from the theoretical framework. Then followed the third chapter, which is based on the analysis of the research samples consisting of (3) samples. The researcher took the descriptive approach to analyzing the samples for the purpose of achieving his results, leading to the fourth chapter of the research, which includes the results of the research. Then the conclusions, sources, and references, concluding the research with an English summary